Genetic and morphological variability in populations of the wild diploid potato species Solanum maglia and Solanum Kurtzianum from Argentina - Marfil, Carlos Federico (2011)
Solanum maglia Schltdl., a wild potato species that has its widest geographical distribution in Chile, is restricted in Argentina to Quebrada La Cumbre (quebrada = gorge), Mendoza province, where no other potato species has been reported. During two collecting expeditions carried out in 2006 and 2007 in this gorge, tubers of two potato populations separated by 500 m (area 1 and 2) were sampled. The morphological and genetic diversity of these two newly sampled populations and of five accessions from the same gorge classified as S. maglia, a plant of Solanum kurtzianum collected outside this gorge, and a Chilean plant of S. maglia were examined by comparing 24 morphological characters and electrophoretic patterns for simple sequence repeat and amplified fragment length polymorphism markers, respectively. Based on the current taxonomic concept, the results support the classification of plants from area 1 as S. kurtzianum and those from area 2 as S. maglia, except for one plant from the former area, which shared electrophoretic bands from both species. This is the first report on the sympatry of populations of the two species in Quebrada La Cumbre. The importance of performing in situ population studies in the same sites over years is discussed.